Synthesis of Polymers Containing 5, 5-Dimethylhydantoin and Study of its Optical Properties - Ali J. Al-Zuhairi (Journal of Global Pharma Technology, 2020)
In this research work, four aromatic polymers, known as 5,5-Dimethylhydantoin  derivatives. 5, 5-dimethylimidazolidine-2,4-dione have been condensed with different dihalolkanes (1,2-dichloroethan and dichloromethane respectively) to give  two different poly hetero aromatic polymers. Also 5,5-dimethylimidazolidine-2,4-dione have been treated with chloroacetic acid and polymerized with ethylene glycol and hydroquinone respectively to give two different polyester polymers. The prepared polymers have been identified using FTIR and 1HNMR instruments. All the prepared polymers have shown a high number average molecular weight (Mn) using Gel Permission Chromatography (GPC) technique. Where absorbance was measured by using a device (UV-Spectroscope).The optical properties of the prepared polymers have been studied. The transmittance, absorption coefficient, had been measured. Transmittance values of the four prepared polymers increases with increasing wavelength due to the decrease in absorption values because the transmittance is inversely proportional with absorbance. The absorbance values of the prepared polymers have been decreased with increasing the wavelength. The absorbance spectra of the polymer solution of the concentration (0.3 g/mL %) for polymer N2 and the concentration (0.2 g/ml %) for polymer N3 within the range (200-1100 nm).The highest absorbance value (310 nm) for polymer N2 and (330 nm) for polymer N3. the absorbance spectra of the polymer solution of the concentration (0.3 g/mL %) for polymer N4 and the concentration (0.2 g/ml %) for polymer N5 within the range (200-1100 nm).The highest absorbance value (310 nm) for polymer N4 and (330 nm) for polymer N5.Keywords: Absorption coefficient 5, 5-Dimethylhydantoin, Optical properties, Polymers.